2021
DOI: 10.48550/arxiv.2105.00621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population Monotonicity in Matching Games

Abstract: A matching game is a cooperative profit game defined on an edge-weighted graph, where the players are the vertices and the profit of a coalition is the maximum weight of matchings in the subgraph induced by the coalition. A population monotonic allocation scheme is a collection of rules defining how to share the profit among players in each coalition such that every player is better off when the coalition expands. In this paper, we study matching games and provide a necessary and sufficient characterization fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…They showed that the core of assignment games is always non-empty, and characterized the core allocations by using matching theory, LP duality theory, and their highly nontrivial interplay. Since then, matching games have attracted a lot of research efforts, and various allocation concepts have been studied within different settings [17,7,6,9,10,21]. In particular, Vazirani [20] studied the approximate core for matching games and achieved the best possible approximate ratio.…”
Section: Our Contributionsmentioning
confidence: 99%
“…They showed that the core of assignment games is always non-empty, and characterized the core allocations by using matching theory, LP duality theory, and their highly nontrivial interplay. Since then, matching games have attracted a lot of research efforts, and various allocation concepts have been studied within different settings [17,7,6,9,10,21]. In particular, Vazirani [20] studied the approximate core for matching games and achieved the best possible approximate ratio.…”
Section: Our Contributionsmentioning
confidence: 99%